Process for utilization of distillation waste biomass of Ocimum sp. - Sarkar, Rohan; Basak, Biraj Bandhu; Banerjee, Atanu (Indian Horticulture, 2023)
Ocimum sp. are commercially cultivated for essential oil. As the oil yield is very low (0.1-0.25 %, w/v), a large amount of waste materials is generated as distillation byproducts. These materials can become a serious concern if not managed properly. Therefore, utilizing the residual biomasses through appropriate valorisation approaches is necessary. In this study, distillation by-products (distillation waste biomass and deodorized water) of two Ocimum sp. were explored for their versatile applications through extraction of phenolic compounds and utilizing the exhaustive biomasses to develop functional material like biochar.